A multi-energy inertia-based coordinated voltage and frequency regulation in isolated hybrid power system using PI-TISMC - Kumar, Kothalanka K. Pavan; Das, Dulal Chandra; Soren, Nirmala; Veerendra, A. S.; Flah, Aymen; Alkuhayli, Abdulaziz; Ullah, Rahmat (Frontiers in Energy Research, 2024)
This paper proposes novel multi-energy inertia support for simultaneous frequency and voltage control of an isolated hybrid power system (IHPS). Multi-energy storage (gas inertia -hydrogen storage, thermal inertia -solar thermal storage, hydro inertia -gravity hydro storage, chemical inertia -battery energy storage) supported by demand side management (DSM) for simultaneous voltage and frequency regulation and backed by biodiesel generators, are the essential elements of IHPS. A novel control strategy of concurrent virtual droop control, virtual damping control, virtual inertia control, and virtual negative inertia control is proposed to utilise multiple inertia sources and to improve LFC & ∆𝑃 $ , ∆𝑇 % , ∆𝑃 & , ∆𝑋 ' , ∆𝑇 ( , ∆𝑃 $' Output states of steam chamber, pressure control, temperature control and thermal storage of ST ∆𝑃 ( , ∆𝑋 "' , ∆𝑋 ""# Output states of governer, TDCand hydraulic turbine of GHPS ∆𝑃 " , ∆𝑋 "( , ∆𝑋 ")# Output states of aqua electrolyzer and hydrogen storage of FC ∆𝑋 * , ∆𝑋 + , ∆𝑋 ) , ∆𝑋 $ , ∆𝛿 , output states of generator field, exciter, amplifier of voltage control